JUSTIFICATION OF THE RHEOLOGICAL OPTIMUM IN THE DEVELOPMENT OF SEMISOLID FORMS. DENTAL GELS - M. N. Anurova; E. O. Bakhrushina; G. G. Barnolitskiy; S. P. Krechetov (Разработка и регистрация лекарственных средств, 2019)
The article presents the results of studying the rheological characteristics of dental preparations in the form of gels registered in the Russian Federation: Dentamet®, Kamistad®, Calgel®, Metragyl-Denta® and Holisal®. The parameters of rheological measurements conducted for dental soft medicinal forms are substantiated. On the basis of the results obtained, optimum rheological characteristics are suggested, which can be recommended for use in the development of dental gels.